2020
DOI: 10.1155/2020/1697657
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐G Polymorphisms Associated with HIV Infection and Preeclampsia in South Africans of African Ancestry

Abstract: Objectives. HLA-G, part of the major histocompatibility complex (MHC), is associated with the risk of developing preeclampsia (PE). In this study, we determined the contribution of specific HLA-G polymorphisms on the risk of developing preeclampsia in HIV-infected and uninfected South Africans of African ancestry. Methods. One hundred and ninety-three women of African ancestry were enrolled (74 HIV-uninfected normotensive, 60 HIV-infected normotensive, 34 HIV-uninfected, and 25 HIV-infected preeclamptics). San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 66 publications
(96 reference statements)
0
11
0
Order By: Relevance
“…Association between HLA-G polymorphism and viral infection has been documented in a number of studies. HLA-G *01:01:08 was reported to be a risk factor for HIV-1 infection in Zimbabwean while 3’UTR 14-bp In/14-bp In was a risk factor for HIV infection in South Africans of African ancestry women ( 70 , 71 ). 14-bp del/14-bp del and HLA-G*01:04:01 /14-bp del genotypes, and UTR-2 and UTR-3 haplotypes were found to be the risk factors for hepatitis C virus ( 72 , 73 ).…”
Section: Induction Of Hla-g Expression In Infectious Diseasesmentioning
confidence: 99%
“…Association between HLA-G polymorphism and viral infection has been documented in a number of studies. HLA-G *01:01:08 was reported to be a risk factor for HIV-1 infection in Zimbabwean while 3’UTR 14-bp In/14-bp In was a risk factor for HIV infection in South Africans of African ancestry women ( 70 , 71 ). 14-bp del/14-bp del and HLA-G*01:04:01 /14-bp del genotypes, and UTR-2 and UTR-3 haplotypes were found to be the risk factors for hepatitis C virus ( 72 , 73 ).…”
Section: Induction Of Hla-g Expression In Infectious Diseasesmentioning
confidence: 99%
“…We found the relationship between the heterozygosity at HLA‐G rs9380142 (chromosome position: 29798794) and an increased risk of HCV susceptibility. In the previous studies, HLA‐G rs9380142 was reported to be associated with the preeclampsia in HIV‐infected women, arthritis hip arthritis and deformity in enthesitis‐related arthritis‐juvenile idiopathic arthritis 28,29 . HLA‐G Rs9380142 maps to the 3′UTR region.…”
Section: Discussionmentioning
confidence: 94%
“…Further studies are needed to confirm whether an association exists between HLA-G 14bp ins/del polymorphism with RIF in patients of other ethnicities. In addition to RIF, maternal HLA-G 14bp ins/del polymorphism is also reported to be associated with preeclampsia ( 95 ), gestational diabetes mellitus ( 96 ), and recurrent miscarriage ( 97 99 ). Almeida et al.…”
Section: Discussionmentioning
confidence: 99%